Focus on diabetic retinopathy in adolescents - Kassem, Ahmed; Asheim, Collin (Acta Biomedica Atenei Parmensis, 2024)
Abstract. Background and aim: Diabetic retinopathy (DR) is a vision threatening and preventable complication of diabetes (DM) that was historically rare in the pediatric population but increasing incidence is noted in the adolescent age group. Methods: In this review, we present the etiology, magnitude of the problem, challenges to screening and new opportunities for early detection Results: The incidence of diabetic retinopathy in children with type 2 DM (T2DM) is estimated to be 6.99% 5 years from diagnosis and the risk of DR in T2DM is twice as much as in T1DM and is significantly higher after puberty. Smart phone-based screening has reported sensitivity and specificity for any DR being 52-92.2% and 73.3-99% respectively. The use of Artificial Intelligence has high sensitivity and specificity for identifying DR greater than 94% and 86% respectively Conclusions: Diabetic retinopathy is increasingly noted in children and adolescents necessitating reconsideration of current guidelines. Technologies such as Smartphone-compatible devices, telemedicine, and use artificial intelligence (AI) show promise in overcoming anticipated shortage in healthcare professionals available for screening.